Respon Pertumbuhan Bibit Kakao (Theobroma cacao L.) terhadapPemberian Pupuk Guano dan KCl - Pispa Rajagukguk; Balonggu Siagian; Ratna Rosanty Lahay (Universitas Sumatera Utara, 2015)
Addition of guano in cultivation of cacao seedling is the one step to use organic fertilizer thatcomes from animal feces and it is used to add soil nutrient for the growth of cocoa seedlings, aswell addition of KCl is used to add soil nutrient too. For that purpose addition guano and KCl aimsto increase growth of cacao in cultivation of seedling. This research had been conducted atexperimental field of agriculture fakulty University of North Sumatera in October 2013 - January2014 using factorial randomized block design with two factor, i.e. addition dose of guano (0, 75 ,150, 225 g/polibag) and dose of KCl (0, 2, 4 g/polibag). Parameter observed were cacao height,cacao stem diameter, cacao leaf number, total leaf area of cacao, shoot fresh weight of cacao, shootdry weight of cacao, root fresh weight of cacao, root dry weight of cacao ,and cacao shoot rootratio. The result showed that parameter cacao height, cacao stem diameter, total leaf area of cacao,shoot fresh weight of cacao, shoot dry weight of cacao, and cacao shoot root ratio weresignificantly to addition guano but total leaf areaof cacao, root fresh weight of cacao, root dryweight of cacao,and cacao shoot root ratio were not significantly to addition guano.The best resultin addition guano is 225 g/polibag that produce shoot dry weight of cacaoas 11.57 g. All parameterswere not significantly to addition KCl and the interaction of two factor. The best resultofcombination is 225 g/polibag of guano and 4 g/polibag of KCl, that produce root dry weight ofcacao as 1.76 g.Keywords :guano, KCl, cacao seedlings.